Student Career Prediction Using Advanced Machine Learning Techniques - Sripath Roy, K; Roopkanth, K; Uday Teja, V; Bhavana, V; Priyanka, J (International Journal of Engineering and Technology, 2018)
As students are going through their academics and pursuing their interested courses, it is very important for them to assess their capabilities and identify their interests so that they will get to know in which career area their interests and capabilities are going to put them in. This will help them in improving their performance and motivating their interests so that they will be directed towards their targeted career and get settled in that. Also recruiters while recruiting the candidates after assessing them in all different aspects, these kind of career recommender systems help them in deciding in which job role the candidate should be kept in based on his/her performance and other evaluations. This paper mainly concentrates on the career area prediction of computer science domain candidates.Â Â